A mobile olfactometer for fMRI-studies - Sommer, Ulrich; Griebe, Martin; Heiser, Clemens; Hörmann, Karl; Stuck, Boris (Journal of neuroscience methods, 2012)
To perform functional magnetic resonance imaging (fMRI) studies with olfactory stimulation, the stimulation device requires special properties including those of being non-conductive and non-magnetic. It should also be easily portable and should be small enough to be stored easily when not in use. However, presently only a limited number of devices fulfill these criteria; additionally, they are typically associated with high costs. The aim of the study was to investigate whether a newly developed and relatively simple and inexpensive stimulation device would be suitable for fMRI measurements. Our stimulation device was made of standard industrial and laboratory components, has open-source software and consists of 3 core compartments namely: ‘the air inlet, control and distribution section’, ‘the odorant-section’, and ‘the delivery-section’. The device was tested in an fMRI study using 21 healthy normosmic subjects who were stimulated with two odors, d-limonene and terpinen-4-ol. Results from this trial suggest that the stimulation device is capable of creating adequate stimulation suitable for fMRI sequences. In general we describe how all sections of the olfactometer are optimized for the needs of fMRI studies.
Gesehen am 04.04.2018